2020
DOI: 10.1111/plb.13098
|View full text |Cite
|
Sign up to set email alerts
|

The role of cyanide‐resistant respiration in Solanum tuberosum L. against high light stress

Abstract: Cyanide-resistant respiration in potato mitochondria is an important pathway for energy dissipation. It can be activated by high light; however, it is unclear what roles cyanide-resistant respiration plays in the response to high light stress in potato.• We designed a CRISPR vector for the functional gene StAOX of the potato cyanide-resistant respiratory pathway. Agrobacterium tumefaciens GV3101 was transformed into potato. Hydrogen peroxide level, MDA content, antioxidant activity and cyanide-resistant respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that stressed wheat plants were distinguished by a two-fold increase in the capacity of the alternative respiratory pathway relative to the control ( Figure 5 F), which, apparently, is important for plants under oxidative stress due to the detection of antioxidant activity in cyanide-resistant oxidase [ 81 ]. Moreover, alternative oxidase has been considered to have a role in improving plant tolerance to multiple environmental stresses [ 52 , 53 ]. Indeed, it was shown that the alternative respiration rate was significantly increased in stressful conditions, for instance, under salt [ 82 ], cold [ 83 ], aluminum [ 84 ], and drought [ 85 ] stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that stressed wheat plants were distinguished by a two-fold increase in the capacity of the alternative respiratory pathway relative to the control ( Figure 5 F), which, apparently, is important for plants under oxidative stress due to the detection of antioxidant activity in cyanide-resistant oxidase [ 81 ]. Moreover, alternative oxidase has been considered to have a role in improving plant tolerance to multiple environmental stresses [ 52 , 53 ]. Indeed, it was shown that the alternative respiration rate was significantly increased in stressful conditions, for instance, under salt [ 82 ], cold [ 83 ], aluminum [ 84 ], and drought [ 85 ] stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cytochrome respiratory pathway common to all eukaryotes, plants contain the cyanide-insensitive alternative respiratory pathway catalyzed by the alternative oxidase (AOX) [ 49 , 50 , 51 ]. Several studies have reported the involvement of AOX in the neutralization of an excessive amount of ROS, as well as the critical role of alternative respiratory pathway in the adaptation of plants to different stresses [ 52 , 53 ]. Thus, cyanide-insensitive respiration was shown to be involved in plant protection against thermogenesis in the flowering of the sacred lotus [ 54 ] and Araceae plants [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that following V. nashicola infection, a much larger increase in the MDA content occurred in the susceptible cultivar Xuehua than in the resistant cultivar Huangguan. MDA is one of the major products of membrane lipid peroxidation [34]. The V. nashicola-induced increase in MDA indicates that damage to the cell membrane system of pear leaves was more serious in Xuehua than in Huangguan.…”
Section: Discussionmentioning
confidence: 99%
“…A CRISPR vector for the functional gene StAOX of the potato cyanide-resistant respiratory pathway was designed to examine the role of cyanide-resistant respiration in potato against high-light stress. The results indicated that high-light stress induced expression of AOX and accelerated cyanide-resistant respiration, and that loss of StAOX directly led to inhibition of cyanide-resistant respiration ( Hua et al, 2020 ).…”
Section: Potato and Application Of Crispr/cas Systemmentioning
confidence: 99%